2022
DOI: 10.4102/sajhrm.v20i0.1620
|View full text |Cite
|
Sign up to set email alerts
|

The influence of training and career development opportunities on affective commitment: A South African higher education perspective

Abstract: Orientation: Employees with affective commitment are significant assets to their organisations because they remain loyal even when faced with attractive external opportunities. Therefore, there is a need to understand how different organisational factors enhance the affective commitment of employees.Research purpose: The study aimed to investigate the impact of training and career development opportunities on affective commitment amongst employees at a selected higher education institution.Motivation of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…Also, training possibilities in another study were found to satisfy workers' needs for professional growth. Employees who possess the most fundamental professional abilities will be more driven to finish their work more effectively, to accomplish more goals, to want to take on more difficult tasks, and to seek out more promotion chances ("Exciting Career Development Opportunity for Early Clinicians," 2022; Muleya et al, 2022). However, despite training programs being established as a crucial element of employee performance, this research did not establish its significant impact on employee loyalty.…”
Section: Coefficientsmentioning
confidence: 84%
See 2 more Smart Citations
“…Also, training possibilities in another study were found to satisfy workers' needs for professional growth. Employees who possess the most fundamental professional abilities will be more driven to finish their work more effectively, to accomplish more goals, to want to take on more difficult tasks, and to seek out more promotion chances ("Exciting Career Development Opportunity for Early Clinicians," 2022; Muleya et al, 2022). However, despite training programs being established as a crucial element of employee performance, this research did not establish its significant impact on employee loyalty.…”
Section: Coefficientsmentioning
confidence: 84%
“…Training is defined as learning activities that help workers improve their present job-related abilities. Muleya et al (2022) defined training as the planned actions carried out by an organization to transfer information and skills acquired on the job, improve employees' attitudes and behaviours, and further the organization's goals.…”
Section: Training and Development Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors might improve the employees' level of affective commitment, such as participation in further training and the firm's support for this training (Grund and Titz 2022). In addition, research found that factors such as the work-life balance of the employees might positively contribute to affective commitment and normative commitment (Botella-Carrubi et al 2021;Muleya et al 2022).…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…To guide the country towards a just and prosperous society (Liu, Dou, Li, & Cai, 2020), we must build the proper infrastructure and facilities and develop professional, ethical, and visionary talents (Tha, 2022). One of our commitments is needs-based, targeted staff training and further education (Muleya, Ngirande, & Terera, 2022). Building Indonesian people must begin with three main paths: developing equitable and quality education, providing access to world-class health services and providing public access to decent jobs and livelihoods.…”
Section: Introductionmentioning
confidence: 99%